Work experience quality and vocational development of students from technological courses - Gamboa, Vitor (2018)
The provision of workplace-based experiences (internship) is an important component of training programs of students attending vocational education courses. Regarding the impact of such experiences in the vocational development, results of the present research are not conclusive enough. Therefore, the main purpose of this study is to clarify the relationship between work experience quality and students vocational development. Using a longitudinal design, we conducted a study that explores the relationship between the perceived qualities of the training experience and the vocational development of Portuguese high school students (N = 196). The results suggest that the work experience quality is relevant for the vocational development of students, mainly, in what concerns the process of career exploration.